In Search of the Babayi: A cartography of a Distinct Filipina Theoethics - Alfonso Jr Pascual Suico (Journal of Asian Orientation in Theology, 2019)
This paper on methodology is an attempt to find a distinct Filipino theology and ethics by retrieving the sense of the babayi (woman). The babayi comes from the ancient Asiatic script called the baybayin. Inspired by the courage and resiliency of the Filipina woman in the face of tragedy and war, the goal is to map out a theo-ethics that is uniquely reflective of the Filipino woman within the broader feminist and liberation ethics. As a method, it critiques the prevailing framing of Western feminism common among Filipino women writers. Following intersectionality, a paradigm that analyzes oppression as the crossroad of racism and poverty, this method locates the Filipina in the multiaxial framing of history, the struggle of poverty and discrimination, displacement, religion and dialogue, and ecology. This multidimensional approach considers the long history of oppression experienced by our people, reflects inherent Filipino values and provides a method for understanding the Filipina and her allies today.Keywords: babayi (woman), intersectionality, feminism, liberation